The relationship between the length of the cupulae of free neuromasts and feeding ability in larvae of the willow shiner Gnathopogon elongatus caerulescens (Teleostei, Cyprinidae - Mukai, Yukinori; Kobayashi, Hiroshi; Yoshikawa, Hiromasa (The Company of Biologists Ltd, 1994)
Free mechanosensory neuromasts of larval fishes have been described as playing a complementary role to vision in feeding behaviour (Disler, 1971; Iwai, 1972a,b). In certain species or under limited conditions, free neuromasts play a major role in detecting prey. The larvae of mottled sculpin Cottus bairdi can feed on Artemia in the dark by using free neuromasts (Jones and Janssen, 1992). Artificially blinded surface-feeding Aplocheilus lineatus can detect insects on the water surface by means of free neuromasts (Muller and Schwarts, 1982; Tittel et al. 1984; Bleckmann, 1988; Bleckmann et al. 1989). Furthermore, vibrations produced by swimming crustaceans are known to be a potent natural stimulus for the lateral line system in the Antarctic fish Pagothenia borchgrevinki (Montgomery and Macdonald, 1987; Montgomery, 1989). We found that larvae of a plankton feeder, the willow shiner Gnathopogon elongatus caerulescens (Sauvage) (Cypriniformes, Cyprinidae), fed on nauplii of Artemia in complete darkness. Ototoxic compounds, such as streptomycin, have been shown to disturb the function of the lateral line organ or free neuromasts (Kaus, 1987; Blaxter and Fuiman, 1989; Janssen, 1990; Jones and Janssen, 1992). Willow shiner larvae treated with streptomycin sulphate no longer feed on Artemia in the dark (Y. Mukai, in preparation). The willow shiner inhabits calm lakes and feeds on zooplanktonic prey (Nakamura, 1949). The larvae show a high sensitivity to minute water displacements. From these observations and from our findings, it appears that larval willow shiner must feed on zooplankton by using free neuromasts in the dark. In larval willow shiner, the vane-like cupulae of the free neuromasts protrude from the body surface and the long cupulae are 100-250 microm in length (Mukai and Kobayashi, 1991). The prey is detected by the free neuromasts as a result of a slight bending of the cupula in response to local water movements. The shape of the cupula, especially its length, must therefore be related to the sensitivity of the free neuromast, as inferred from the results of Coombs and Janssen (1989) and van Netten and Kroese (1989).